Functional Impacts of the Intestinal Microbiome in the Pathogenesis of Inflammatory Bowel Disease. Issue 1 (January 2015) - Li, Jennifer; Butcher, James; Mack, David; Stintzi, Alain
Abstract : Abstract: The human intestinal microbiome plays a critical role in human health and disease, including the pathogenesis of inflammatory bowel disease (IBD). Numerous studies have identified altered bacterial diversity and abundance at varying taxonomic levels through biopsies and fecal samples of patients with IBD and diseased model animals. However, inconsistent observations regarding the microbial compositions of such patients have hindered the efforts in assessing the etiological role of specific bacterial species in the pathophysiology of IBD. These observations highlight the importance of minimizing the confounding factors associated with IBD and the need for a standardized methodology to analyze well-defined microbial sampling sources in early IBD diagnosis. Furthermore, establishing the linkage between microbiota compositions with their function within the host system can provide new insights on the pathogenesis of IBD. Such research has been greatly facilitated by technological advances that include functional metagenomics coupled with proteomic and metabolomic profiling. This review provides updates on the composition of the microbiome in IBD and emphasizes microbiota dysbiosis-involved mechanisms. We highlight functional roles of specific bacterial groups in the development and management of IBD. Functional analyses of the microbiome may be the key to understanding the role of microbiota in the development and chronicity of IBD and reveal new strategies for therapeutic intervention. Abstract : Article first published online 21 September 2014.